El progreso en medicina y la inteligencia artificial. - Viniegra-Velázquez, Leonardo (Boletín Médico del Hospital Infantil de México)
This essay questions, with regard to medicine, the idea of progress as technological development by focusing on people rather than things. It analyzes how the predominance of such an idea of progress converts today's societies to techno-fetishism that degrades community life and medical practice, contributing to the medicalization of social life. It is argued that the realization of technological potentialities depends on their forms of use; that the main motive of technological development is unlimited profit and that priority developments are those that enhance the social control that maintains the status quo. The intelligence as an intelligence quotient is criticized by proposing it as an attribute of the human being as a whole, manifested in the ways of thinking and proceeding of people in their circumstances, where affectivity and critical thinking are essential for their development; it is emphasized that its antecedent is the harmonic concert of planetary life that contrasts with the prevailing human disharmony. It is proposed that artificial intelligence is the most recent creation of techno-fetishism that deposits vital attributes in technology and that its forms of use will accentuate the degradation of human and planetary life. Another idea of medical progress is proposed, based on forms of organization conducive to the development of inquisitive, critical and collaborative skills that promote permanent improvement, whose distant horizon is dignifying progress: spiritual, intellectual, moral and convivial sublimation of collectivities in harmony with the planetary ecosystem.